Recent advances and future perspectives of CAR-T cell therapy in head and neck cancer - Hu, Chunmei; Liu, Min; Li, Yutao; Zhao, Yi; Sharma, Amit; Liu, Haotian; Schmidt-Wolf, Ingo G. H. (Frontiers in Immunology, 2023)
Head and neck cancer (HNC) ranks as the sixth most prevalent type of cancer globally and accounts for about 4% of all types of cancer. Among all HNC, most are head and neck squamous cell carcinoma (HNSCC) with clinical therapies that include surgery, radiation therapy, chemotherapy, immunotherapy, targeted therapy, and multimodal treatments. In recent years, chimeric antigen receptor (CAR)-T cell immunotherapy has significantly transformed the therapeutic approaches for leukemia and lymphoma and has garnered increased attention as a potential treatment for a wide range of cancers. However, CAR-T immunotherapy in solid tumors, especially HNSCCs, lags significantly behind due to the paucity of tumor-specific antigens, high levels of tumor heterogeneity, immunosuppressive tumor microenvironment, the risk of treatment-related toxicities and off-target adverse events in HNSCCs. The objective of this review is to explore the advancement of CAR-T cell therapy in the treatment of HNSCCs. We aim to outline the targeted antigens in HNSCCs, highlight the challenges and potential solutions, and discuss the relevant combination therapies. Our review presents a comprehensive overview of the recent developments in CAR-T cell therapy for HNSCCs, and provides valuable insights into future research avenues.